2017
DOI: 10.1038/srep45748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Vernalization- and Cytokinin-Induced Floral Transition in Dendrobium nobile

Abstract: Vernalization is required for floral initiation in Dendrobium. Interestingly, those beneficial effects can also be achieved by exogenous cytokinin application in greenhouses. Thus, an as yet unknown crosstalk/interaction may exist between vernalization and cytokinin signaling pathways. In this study, we showed, by de novo transcriptome assembly using RNA-seq data from both vegetative and reproductive tissue samples, that some floral transition-related genes—DnVRN1, FT, SOC1, LFY and AP1—were differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
22
0
3
Order By: Relevance
“…Previously, transcriptomic analysis of flower development demonstrated that floral organ development is regulated by GA signaling in Gerbera hybrida [60]. In Dendrobium nobile, comparative transcriptomic analysis revealed that DEGs of GA signaling pathways are involved in floral transition [61]. These previous studies and our data suggest that key genes of GA signaling and metabolism pathways are associated with flower bud differentiation.…”
Section: Expression Analysis Of Key Differentially Expressed Genes (Dsupporting
confidence: 77%
“…Previously, transcriptomic analysis of flower development demonstrated that floral organ development is regulated by GA signaling in Gerbera hybrida [60]. In Dendrobium nobile, comparative transcriptomic analysis revealed that DEGs of GA signaling pathways are involved in floral transition [61]. These previous studies and our data suggest that key genes of GA signaling and metabolism pathways are associated with flower bud differentiation.…”
Section: Expression Analysis Of Key Differentially Expressed Genes (Dsupporting
confidence: 77%
“…Transcriptome analysis is an effective approach to study flowering pathway genes [ 23 , 24 ]. Using this approach, DEGs in response to vernalization have been identified in Japanese pear ( Pyrus pyrifolia Nakai) and oriental lily [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on expression analyses and functional studies with heterologous expression systems, candidate genes for flowering regulatory networks in orchids have been reported. Recently, genome-wide analyses have also been taken into consideration for the identification of Orchidaceae-specific and/or species-specific key genes controlling flowering/flower development of orchids (Huang et al, 2016; Lin et al, 2016; Wen et al, 2017).…”
Section: Floral Transition Of Orchidsmentioning
confidence: 99%
“…Expression of DOMADS1 was up-regulated in transgenic plants harboring p 35S : antisense DOH1 suggesting that DOH1 is a possible upstream repressor of DOMADS1 in the flowering control of Dendrobium orchids. Recently, transcriptomes of D. nobile were analyzed under cold (4 °C) or exogenous cytokinin (thidiazuron) treatment (Wen et al, 2017). The results showed that SOC1 , LFY and AP1 genes were induced by both low temperature and thidiazuron treatment whereas DnVRN1 and FT were induced only by cold treatment.…”
Section: Floral Transition Of Orchidsmentioning
confidence: 99%